2005
DOI: 10.1007/s10722-004-4635-1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Phenotypic Profiles in Landrace Populations of Vietnamese Rice: A Case Study of Agronomic Characters for Conserving Crop Genetic Diversity on Farm

Abstract: Phenotypic variation of agronomic characters in aromatic rice (Oryza sativa L.) was analyzed in order to elucidate the genetic diversity of the populations of rice landraces. Thirteen populations in Namdinh province, in the Red River Delta of Vietnam, were studied in both of farmers' fields and an experimental field. Only small differences were found in agronomic characters among the populations, including populations containing different varieties. Variations among the populations in the frequency distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 8 publications
(6 reference statements)
2
20
0
Order By: Relevance
“…It also revealed that no duplicate existed among the genotypes for the studied characters. Fukuoka et al (2006), Hossain (2008), Sarhadi et al (2009) and Nascimento et al (2011) earlier also found no duplicates from cluster analysis using Mahalanobis' D 2 statistics in rice. The clustering pattern also revealed that the genotypes constellated in the cluster were not originated from the same geographic region.…”
Section: Methodsmentioning
confidence: 93%
“…It also revealed that no duplicate existed among the genotypes for the studied characters. Fukuoka et al (2006), Hossain (2008), Sarhadi et al (2009) and Nascimento et al (2011) earlier also found no duplicates from cluster analysis using Mahalanobis' D 2 statistics in rice. The clustering pattern also revealed that the genotypes constellated in the cluster were not originated from the same geographic region.…”
Section: Methodsmentioning
confidence: 93%
“…In the study with aromatic rice landraces, Fukuoka et al (2006) concluded that significant variation may be found among genotypes with the same name. According to Li et al (2002) diversity analysis based on phenotypic values may not be the perfect representation of the natural groupings of cultivars, because the phenotypic characters are influenced by environmental.…”
Section: Genetic Diversity Analysismentioning
confidence: 99%
“…Morphological traits are directly related to the interaction between a species and its environment (Westoby and Wright 2006). Morphology includes some of the most accessible and functionally important traits, with the potential to be measured for each species (Fukuoka et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Yawen et al (2003) studied the genetic diversity on 5285 accessions of indigenous rice in China and found considerable morphological variation among accessions. In India, Patra and Dhua (2003) analyzed the agro-morphological diversity of upland rice and in Vietnam, Fukuoka et al (2006) assessed the variability in agronomic characters among landraces of aromatic rice populations. Using 42 agro-morphological characters associated with 39 SSR markers, Bajracharya et al (2006) examined the genetic relationships among 147 high altitude rice landraces from Jumla, Nepal.…”
Section: Introductionmentioning
confidence: 99%